Treatment of acidic palm oil for fatty acid methyl esters production - Hayyan, Adeeb; Mjalli, Farouq Sabri; Mirghani, Mohamed Elwathig Saeed; Hashim, Mohd Ali; Hayyan, Maan; Alnashef, Inas Muen; Al-Zahrani, Saeed M. (Slovenska Akademia Vied * Chemicky Ustav, 2012)
Acidic crude palm oil (ACPO) produced from palm oil mills with an acid value of 18 mg g−1 was considered to be a possible feedstock for biodiesel production. Due to its high acidity, conventional transesterification cannot be applied directly for biodiesel production. Methane sulphonic acid (MSA, CH3SO3H) is used to reduce the acidity prior to the alkaline transesterification reaction. The laboratory-scale experiments involved an MSA to ACPO dosage of 0.25–3.5 %, a molar ratio (methanol to ACPO) from 4: 1 to 20: 1, reaction temperature of 40–80°C, reaction time of 3–150 min, and stirrer speed of 100–500 min−1. The optimum esterification reaction conditions were 1 % of catalyst to ACPO, with a molar ratio of methanol to ACPO of 8: 1, a stirring speed of 300 min−1, for 30 min and at 60°C. Under these conditions, the FFA content was reduced from 18 mg g−1 to less than 1 mg g−1 and with a yield of 96 %. The biodiesel produced met the EN14214 standard specifications. MSA was recycled for three times without losing its activity. The biodiesel produced in a two-stage process has a low acid value (0.14 mg g−1).